Preparation method and application of metal ion-doped ultra-small cerium oxide polishing abrasive

By doping metal ions in ceria polishing abrasives and synthesizing mesoporous ceria nanospheres by high-temperature thermal decomposition method, the problem of uneven shape and size of existing ceria polishing abrasives in integrated circuit manufacturing is solved, and more efficient polishing performance and surface quality are achieved.

CN119775963AActive Publication Date: 2025-04-08FUDAN UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411943190.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-08
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The existing cerium oxide polishing abrasives have problems of uneven shapes and inconsistent sizes in the manufacturing of integrated circuits, which leads to scratches easily during the polishing process and affects the surface quality of the product.

Method used

Mesoporous cerium oxide nanospheres doped with metal ions were synthesized by high-temperature thermal decomposition in co-solvents of ethanol and 1-octene, and then calcined to obtain spherical or spherical cerium oxide polishing abrasives.

Benefits of technology

The prepared cerium oxide polishing abrasives doped with metal ions have the characteristics of uniform morphology and controllable particle size, which improves polishing performance and surface quality, and achieves efficient integrated circuit chip polishing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775963A_ABST
    Figure CN119775963A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of an ultra-small cerium oxide polishing abrasive doped with metal ions. According to the preparation method, cerium nitrate hexahydrate is taken as a precursor, trioctylphosphine oxide is taken as a ligand, hydrated metal nitrate is doped, ethanol is taken as a cosolvent, the substances are mixed and dissolved, 1-octadecene is added, and metal-doped mesoporous cerium oxide nanospheres are obtained through a high-temperature thermal decomposition method; and calcining to obtain the polishing abrasive. According to the preparation method of the ultra-small cerium oxide polishing abrasive doped with the metal ions, the cerium oxide nano abrasive which is uniform in morphology, controllable in size and capable of being doped with other metal ions is prepared, and after the metal ions are doped, the surface activity of cerium oxide is further enhanced, so that the surface activity of cerium oxide is further improved. The content of trivalent cerium ions in a sample doped with Gd is increased to 31.0%, and the polishing rate of 342 nm / min can be achieved under the low solid content without adding any dispersing aid to the polishing solution prepared from the grinding material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of ultra-small cerium oxide polishing abrasive doped with metal ions, belonging to the technical field of polishing materials. Background Art

[0002] Cerium is the most active rare earth element among the lanthanide elements except europium, and is also the rare earth element with the highest reserves in the earth's crust. 2 ) is the most widely used cerium compound and has good redox properties. CeO 2 There are two mixed valence states of trivalent and tetravalent cerium ions in the unit cell, which can achieve reversible conversion between trivalent and tetravalent states through the generation or elimination of oxygen vacancies. Therefore, it has excellent redox, oxygen transport, oxygen storage and release capabilities. The unique properties of cerium oxide make it have antibacterial, anti-inflammatory, anti-tumor and enzyme-mimicking biomedical activities, and can be used for the diagnosis and treatment of various diseases. 2 It can also be used as a carrier combined with other active metals to show unique catalytic properties, and is widely used in organic synthesis, tail gas purification and other fields. In addition to its applications in biology and catalysis, CeO 2 Nanoparticles have high surface reactivity and super strong adsorption capacity, and can be used as polishing abrasives in the field of chemical mechanical polishing.

[0003] Chemical mechanical polishing (CMP) is an ultra-precision surface processing technology. The basic principle is to bring the material surface into contact with the polishing liquid. The polishing liquid contains active substances that can react chemically with the wafer surface, forming a layer of soluble substances on the material surface, and then removing this layer of soluble substances from the surface through mechanical force. Therefore, chemical mechanical polishing can combine the chemical corrosion of the oxidant and the mechanical grinding of the nanoabrasive to remove materials at the nano and atomic scales, thereby obtaining an ultra-smooth and ultra-low damage surface. This polishing technology has been widely used in optical components, computer hard disks, micro-electromechanical systems, integrated circuits and other fields. Among them, in the integrated circuit manufacturing process, CMP technology is one of the key core technologies, which has a significant impact on the production capacity and quality of downstream chips. From the perspective of current demand, with the reduction of integrated circuit feature size and the increase of integration, better surface flatness is required, which puts higher requirements on polishing technology.

[0004] In the polishing process, abrasive is one of the most important core components. At present, a series of abrasives have been developed, including silicon oxide, aluminum oxide, cerium oxide and some composite materials, etc. However, as the feature size of semiconductor technology continues to decrease, the polishing process requires abrasives with high selectivity and low defect levels while ensuring high polishing rates. 2) is one of the most widely used abrasive particles in CMP polishing liquid and has been widely used in traditional dielectric polishing processes of integrated circuits (ICs), such as CMP of shallow trench isolation (STI) and interlayer dielectric (ILD). 2 Abrasives can remove dielectric materials under the combined action of mechanical wear and surface chemical reaction. The material removal rate depends not only on the additives in the slurry, but also on the pH value of the slurry and the CeO 2 Therefore, improving CeO 2 One way to improve the CMP performance of abrasives is to improve CeO 2 Characteristics of abrasive particles. Currently, a series of cerium oxide polishing abrasives have been developed, most of which are obtained by calcination, precipitation and sol-gel methods. However, the crystal growth is difficult to control, resulting in different shapes and sizes of abrasives. In addition, it is more difficult to prepare spherical abrasives, so scratches are easily generated during the polishing process, which greatly affects the performance of the subsequent products. Therefore, it is necessary to develop a spherical or quasi-spherical cerium oxide polishing abrasive with uniform size; at the same time, improve the surface quality of the polished product. Summary of the invention

[0005] 1. Technical issues to be resolved

[0006] In order to solve the above problems in the prior art, the present invention provides a preparation method of ultra-small cerium oxide polishing abrasive doped with metal ions and application thereof.

[0007] (II) Technical solution

[0008] In order to achieve the above object, the main technical solutions adopted by the present invention include:

[0009] A method for preparing ultra-small cerium oxide polishing abrasive doped with metal ions, comprising the following steps: S1, using hexahydrated cerium nitrate as a precursor, trioctylphosphine oxide as a ligand, doping hydrated metal nitrate, using ethanol as a cosolvent, mixing and dissolving the above substances, and then adding solvent 1-octadecene, and obtaining mesoporous cerium oxide nanospheres doped with metal ions by high-temperature thermal decomposition;

[0010] S2. The polishing abrasive of the mesoporous cerium oxide nanospheres doped with metal ions can be obtained by calcining the mesoporous cerium oxide nanospheres doped with metal ions.

[0011] In the preparation method as described above, preferably, in step S1, the hydrated metal oxynitrate is any one or more of hydrated gadolinium nitrate, hydrated zirconium oxynitrate, hydrated neodymium nitrate, hydrated ytterbium nitrate, hydrated lanthanum nitrate or hydrated yttrium nitrate.

[0012] In the preparation method as described above, preferably, in step S1, the addition ratio of the cerium nitrate hexahydrate, trioctylphosphine oxide and hydrated metal oxynitrate is 17-19:20-30:1-3 in molar ratio.

[0013] Through a large number of experimental studies, it is found that when the addition ratio of hexahydrate cerium nitrate to hydrated metal oxynitrate is lower than 19:1 in molar ratio, effective doping cannot be achieved, and the effect of increasing the content of trivalent cerium ions in the product is not obvious. When it is higher than 17:3, it will affect the morphology of the product in the present invention, resulting in a decrease in the polishing performance of the material. Therefore, the addition ratio of hexahydrate cerium nitrate to hydrated metal oxynitrate is preferably 17-19:1-3 in molar ratio.

[0014] In the preparation method as described above, preferably, in step S1, the temperature for mixing and dissolving the aforementioned substances is 80° C., and the molar ratio of the 1-octadecene to the cerium nitrate hexahydrate is 40 to 150:1.

[0015] In the preparation method as described above, preferably, in step S1, the high temperature thermal decomposition method is carried out at 180°C to 260°C, and the reaction time is 30 to 60 minutes.

[0016] In the preparation method as described above, preferably, in step S2, the calcination temperature is 480° C. to 550° C., and the calcination time is 1.5 to 4 hours.

[0017] The preparation method described above can obtain spherical or quasi-spherical cerium oxide polishing abrasive with uniform morphology, a particle size of 15 to 30 nm, and doped with metal ions.

[0018] The ultra-small cerium oxide polishing abrasive doped with metal ions obtained by the preparation method described above is used in the preparation of polishing liquid.

[0019] In the application as described above, preferably, the mass concentration of the ultra-small cerium oxide polishing abrasive doped with metal ions in the polishing liquid is 0.15% to 0.5%, the solvent of the polishing liquid is water, and the pH value of the polishing liquid is 4 to 5.

[0020] A polishing liquid comprises ultra-small cerium oxide polishing abrasive doped with metal ions obtained by the preparation method as described above.

[0021] Furthermore, the concentration of the ultra-small cerium oxide polishing abrasive in the polishing liquid is 0.15% to 0.5% by mass, and the pH value is 4 to 5.

[0022] (III) Beneficial effects

[0023] The beneficial effects of the present invention are:

[0024] The present invention provides a method for preparing a super small cerium oxide polishing abrasive doped with metal ions. The polishing abrasive prepared is a spherical cerium oxide nanoabrasive with uniform morphology, controllable size and dopability for other metal ions. The super small cerium oxide doped with metal ions obtained in the preparation method provided by the present invention has a high Ce content. 3+ The presence of CeO helps to break the Si-O bond during the CMP process, resulting in a high removal rate of silicon dioxide. Therefore, the removal rate of CeO can be increased by reducing the particle size and introducing dopants. 2 Center 3+ The content helps to optimize its polishing performance. Therefore, the present invention prepares an ultra-small cerium oxide nanoabrasive with uniform morphology and controllable size, which helps to improve the surface quality after CMP, and optimizes the polishing rate by doping other metal ions to achieve efficient polishing of integrated circuit chips.

[0025] The ultra-small cerium oxide polishing abrasive doped with metal ions prepared by the preparation method of the present invention further enhances the surface activity of cerium oxide after being doped with metal ions. After being doped with gadolinium (Gd), the content of trivalent cerium ions in the sample rises to 31.0%. The polishing liquid prepared with this abrasive can achieve a polishing rate of up to 342 nm / min at a lower solid content without adding any dispersant, and the surface quality of the wafer after polishing is better. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a TEM image of nano-cerium oxide prepared in Example 1 of the present invention;

[0027] Figure 2 This is the XRD spectrum of nano-cerium oxide prepared in Example 1 of the present invention;

[0028] Figure 3 This is a TEM image of commercial nano-cerium oxide in Comparative Example 2 of the present invention;

[0029] Figure 4 This is the XPS spectrum of nano-cerium oxide prepared in Example 1 of the present invention;

[0030] Figure 5 This is the AFM 3D image of the silicon wafer surface before polishing;

[0031] Figure 6 This is the AFM 3D image of the silicon wafer surface obtained after polishing the commercial material in Comparative Example 2.

[0032] Figure 7 This is an AFM 3D image of the silicon wafer surface after polishing using the material of Example 1. DETAILED DESCRIPTION

[0033] The preparation method provided by the present invention uses hexahydrated cerium nitrate as a precursor, trioctylphosphine oxide as a ligand, doped with hydrated metal nitrate, and ethanol as a cosolvent in 1-octadecene to obtain mesoporous cerium oxide nanospheres doped with metal ions by high-temperature thermal decomposition, wherein an appropriate metal ion doping concentration is conducive to CeO 2 Surface defects (Ce 3+ and oxygen vacancies). When impurity ions are introduced into the matrix lattice, its lattice parameters will change. 2 Part of the main body of the crystal Ce 4+ ions are replaced by metal ions, resulting in CeO 2 The local lattice expansion of the crystal promotes oxygen vacancies and Ce 3+ The formation of CeO 2 In the present invention, selecting a suitable metal ion doping concentration is beneficial to achieve CeO 2 In order to optimize the performance, when the concentration of doped metal ions is too low, the content of trivalent cerium ions cannot be effectively increased, and when the concentration of doped metal ions is too high, the solubility limit of metal ions in cerium oxide crystals will be exceeded, and the morphology of cerium oxide nanoparticles will be affected, which is not conducive to the improvement of polishing performance. Therefore, the preferred addition ratio of hexahydrate cerium nitrate to hydrated metal oxynitrate in the present invention is 17-19:1-3 in molar ratio.

[0034] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.

[0035] Example 1

[0036] (1) Take a 100 mL single-mouth round-bottom flask as a reaction vessel, add 9.5 mmol of cerium nitrate hexahydrate, 0.5 mmol of gadolinium nitrate hexahydrate and 12 mmol of trioctylphosphine oxide in sequence, then add 40 mL of ethanol as a cosolvent, and heat the solution to 80°C to completely dissolve the solid. Add 25 mL of 1-octadecene solution at 80°C, and heat to 200°C for half an hour. Collect the product by centrifugation, wash with ethanol several times to remove residual reactants. Then dry it in an oven at 80°C overnight.

[0037] (2) Using a muffle furnace, the material obtained in step (1) was heated to 500° C. at a rate of 1° C. / min in air and calcined for 2 hours to obtain yellow mesoporous cerium oxide nanospheres doped with metallic gadolinium.

[0038] (3) Using a transmission electron microscope (TEM, HT7700 Exalens), take an electron microscope photograph of the nanomaterial obtained in step (2). Figure 1As shown, it can be seen that the prepared cerium oxide has a good and uniform mesoporous spherical morphology, and the material particle size ranges from 20 to 30 nm.

[0039] (4) The crystal structure of the cerium oxide particles obtained in step (2) was measured by X-ray diffraction spectroscopy (XRD, Bruker), and the data was processed using Jade 6.0 software to obtain Figure 2 The results shown show that the characteristic peaks of the sample are consistent with the cerium oxide standard PDF card, confirming the formation of the cubic fluorite crystal phase of the product.

[0040] Example 2

[0041] (1) Take a 100 mL single-mouth round-bottom flask as a reaction vessel, add 9 mmol of cerium nitrate hexahydrate, 1 mmol of gadolinium nitrate hexahydrate and 12 mmol of trioctylphosphine oxide in sequence, then add 40 mL of ethanol as a cosolvent, and heat the solution to 80°C to completely dissolve the solid. Add 25 mL of 1-octadecene solution at 80°C, and heat to 200°C for half an hour. Collect the product by centrifugation, wash with ethanol several times to remove residual reactants. Then dry it in an oven at 80°C overnight.

[0042] (2) The material obtained in step (1) was heated to 500° C. at a rate of 1° C. / min in air and calcined for 2 hours using a muffle furnace to obtain yellow mesoporous cerium oxide nanospheres doped with metallic gadolinium. The particle size of the material was measured to be in the range of 20 to 30 nm using a transmission electron microscope.

[0043] Example 3

[0044] (1) Take a 100 mL single-mouth round-bottom flask as a reaction vessel, add 9.5 mmol of cerium nitrate hexahydrate, 0.5 mmol of zirconium oxynitrate hydrate and 12 mmol of trioctylphosphine oxide in sequence, then add 40 mL of ethanol as a cosolvent, and heat the solution to 80°C to completely dissolve the solid. Add 25 mL of 1-octadecene solution at 80°C, and heat to 200°C for half an hour. Collect the product by centrifugation, wash with ethanol several times to remove residual reactants. Then dry it in an oven at 80°C overnight.

[0045] (2) The material obtained in step (1) was heated to 500° C. at a rate of 1° C. / min in air using a muffle furnace and calcined for 2 hours to obtain yellow mesoporous cerium oxide nanospheres doped with metal zirconium. The particle size of the material was measured to be in the range of 20 to 30 nm using a transmission electron microscope.

[0046] Example 4

[0047] (1) Take a 100 mL single-mouth round-bottom flask as a reaction vessel, add 9 mmol of cerium nitrate hexahydrate, 1 mmol of zirconium oxynitrate hydrate and 12 mmol of trioctylphosphine oxide in sequence, then add 40 mL of ethanol as a cosolvent, and heat the solution to 80°C to completely dissolve the solid. Add 25 mL of 1-octadecene solution at 80°C, and heat to 200°C for half an hour. Collect the product by centrifugation, wash with ethanol several times to remove residual reactants. Then dry it in an oven at 80°C overnight.

[0048] (2) The material obtained in step (1) was heated to 500° C. at a rate of 1° C. / min in air using a muffle furnace and calcined for 2 hours to obtain yellow mesoporous cerium oxide nanospheres doped with metal zirconium. The particle size of the material was measured to be in the range of 15 to 20 nm using a transmission electron microscope.

[0049] Comparative Example 1

[0050] (1) Take a 100 mL single-mouth round-bottom flask as a reaction vessel, add 10 mmol of cerium nitrate hexahydrate and 12 mmol of trioctylphosphine oxide in sequence, then add 40 mL of ethanol as a cosolvent, and heat the solution to 80°C to completely dissolve the solid. Add 30 mL of 1-octadecene solution at 80°C, and heat to 180°C for half an hour. Collect the product by centrifugation, wash with ethanol several times to remove residual reactants, and then dry it in an oven at 80°C overnight.

[0051] (2) The reactant obtained in step (1) was heated to 500° C. at a rate of 1° C. / min in air and calcined for 2 hours using a muffle furnace to obtain a yellow mesoporous cerium oxide powder. The particle size of the material was measured to be in the range of 20 to 30 nm using a transmission electron microscope.

[0052] Comparative Example 2

[0053] Commercially available nano-cerium oxide (≥99.5% metals basis, 20-50nm) was calcined in a muffle furnace at 1°C / min in air at 500°C for 2 hours to obtain a white powder. The electron microscope photographs taken using a transmission electron microscope (TEM, HT7700 Exalens) are shown in the figure below. Figure 3 As shown, obvious particle agglomeration can be seen, and the particles are uneven in size and shape.

[0054] Test Example 1

[0055] The nano-cerium oxide powder prepared in Example 1 was tested using an X-ray photoelectron spectrometer (XPS, AXIS Kratos Supra+), and the obtained data was processed by peak separation using Avantage software to obtain Figure 4 As shown in the results, 10 deconvoluted peaks can be identified in the XPS spectrum of the visible material, among which v 0,v′,u′,u 0 The peak corresponds to Ce 3+ The characteristics of v, v″, v′, u, u″, u′ correspond to Ce 4+ 。 3+ The surface concentration of Ce is determined by the following formulas (1)-(3). Where C and A represent concentration and area, respectively. 3+ The content of Ce is calculated as 3+ The area and Ce 3+ and Ce 4+ The ratio of the sum of the areas of two peaks.

[0056] C(Ce 3+ )=A(Ce 3+ ) / [A(Ce 3+ )+A(Ce 4+ )] (1)

[0057] A(Ce 3+ )=A(v 0 )+A(v′)+A(u 0 )+A(u′) (2)

[0058] A(Ce 4+ )=A(v)+A(v″)+A(v″′)+A(u)+A(u″)+A(u″′) (3)

[0059] The same test was performed on the nano cerium oxide prepared in Examples 2 to 4 and Comparative Example 1, and the Ce content of the cerium oxide material prepared in each example was calculated. 3+ The contents are shown in Table 1.

[0060] Table 1 Nano cerium oxide Ce prepared in each embodiment and comparison example 3+ content

[0061] Serial number <![CDATA[Ce 3+ Content]]> Example 1 25.7% Example 2 31.0% Example 3 23.7% Example 4 24.2% Comparative Example 1 21.5%

[0062] It can be seen from Table 1 that after doping with other metal ions, Ce in nano-cerium oxide 3+ The increased content and enhanced surface activity are beneficial to improving the CMP performance of cerium oxide.

[0063] Test Example 2

[0064] (1) The nano cerium oxide powders prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were dissolved in deionized water to prepare polishing liquids with a mass concentration of 0.2%, and the pH value of each polishing liquid was adjusted to 4.0 using acetic acid. A GNP POLI-400L polishing machine was used for testing, with a polishing head pressure of 3 psi, a turntable speed of 87 rpm, a pressure head speed of 93 rpm, a polishing time of 1 min, and a polishing liquid flow rate of 150 mL / min. A 4-inch silicon wafer with an oxide layer thickness of 1000 nm was polished.

[0065] (2) The oxide layer of the silicon wafer before and after polishing was measured using a FilmExpert film thickness meter (Premier 50). The material removal rate was calculated according to the change in film thickness before and after polishing using formula (4). The results are shown in Table 2.

[0066] Material removal rate = (film thickness before polishing (nm) - film thickness after polishing (nm)) / polishing time (min) (4)

[0067] Table 2 CMP removal rate of nano cerium oxide materials in various embodiments and comparative examples

[0068]

[0069]

[0070] The above results show that compared with the commercially available cerium oxide material in Comparative Example 2, the spherical mesoporous cerium oxide nanomaterial prepared in the present embodiment can achieve a higher material removal rate. At the same time, it can be seen that the removal rate of the nano cerium oxide material doped with other metal ions is significantly improved, and it has excellent polishing performance. And within a certain range of doped metal ion concentration, the more the doping amount, the higher the content of trivalent cerium ions. Among them, the Ce content of the material obtained in Example 4 is 3+ The content is higher than that of the material obtained in Example 3, but since the particle size of the material particles decreases when it is doped with a higher concentration of zirconium ions, the polishing rate of small particles decreases, so its material removal rate is lower than that of Example 3.

[0071] Test Example 3

[0072] The surface quality of the silicon wafer before and after polishing was tested using a fast scanning atomic force microscope (AFM, Dimension FastScan Bio), with a scanning range of 5×5μm 2 The AFM 3D image of the silicon wafer surface before polishing is shown below: Figure 5 As shown in the figure, it can be seen that the surface before polishing is rough and has large ups and downs. The surface arithmetic average roughness Ra = 0.671nm is obtained by using NanoScope Analysis software. The AFM 3D image of the silicon wafer surface obtained after polishing with the commercial material of Comparative Example 2 is as follows Figure 6 As shown in FIG. 1 , it can be seen that the surface quality has improved compared to that before polishing, but the roughness is still relatively large, Ra = 0.382 nm. The AFM 3D image of the silicon wafer surface obtained after polishing using the material prepared in Example 1 of the present invention is as follows: Figure 7 As shown, it can be seen that a flat and smooth surface is produced, and the surface roughness Ra=0.187nm is obtained by analysis, which is about 0.2nm lower than the roughness of commercial materials, and the surface polishing is achieved at an atomic scale of less than 0.2nm. This shows that after CMP using the abrasive prepared by the present invention, a higher surface quality can be obtained, and a higher surface quality has a better guarantee for the later performance of the product and the qualified rate of the product.

[0073] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any person skilled in the art can use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing ultra-small cerium oxide polishing abrasive doped with metal ions, characterized in that: It includes the following steps: S1. Using cerium nitrate hexahydrate as a precursor, trioctylphosphine oxide as a ligand, doping with hydrated metal nitrate, using ethanol as a cosolvent, mixing and dissolving the above substances, and then adding solvent 1-octadecene, and obtaining mesoporous cerium oxide nanospheres doped with metal ions by high-temperature thermal decomposition; S2. The polishing abrasive of the mesoporous cerium oxide nanospheres doped with metal ions can be obtained by calcining the mesoporous cerium oxide nanospheres doped with metal ions.

2. The preparation method according to claim 1, characterized in that In step S1, the hydrated metal nitrate is any one or more of hydrated gadolinium nitrate, hydrated zirconium oxynitrate, hydrated neodymium nitrate, hydrated ytterbium nitrate, hydrated lanthanum nitrate or hydrated yttrium nitrate.

3. The preparation method according to claim 1, characterized in that: In step S1, the cerium nitrate hexahydrate, trioctylphosphine oxide and hydrated metal nitrate are added in a molar ratio of 17-19:20-30:1-3.

4. The preparation method according to claim 1, characterized in that: In step S1, the temperature for mixing and dissolving the aforementioned substances is 80°C, and the molar ratio of 1-octadecene to cerium nitrate hexahydrate is 40 to 150:

1.

5. The preparation method according to claim 1, characterized in that: In step S1, the high temperature thermal decomposition method is to react at 180°C to 260°C for 30 to 60 minutes.

6. The preparation method according to claim 1, characterized in that: In step S2, the calcination temperature is 480°C to 550°C, and the calcination time is 1.5 to 4 hours.

7. Use of the ultra-small cerium oxide polishing abrasive doped with metal ions obtained by the preparation method according to any one of claims 1 to 6 in preparing a polishing liquid.

8. The use according to claim 7, characterized in that The mass concentration of the metal ion-doped ultra-small cerium oxide polishing abrasive in the polishing liquid is 0.15%-0.5%, the solvent of the polishing liquid is water, and the pH value of the polishing liquid is 4-5.

9. A polishing liquid comprising ultra-small cerium oxide polishing abrasive doped with metal ions obtained by the preparation method according to any one of claims 1 to 6.

10. The polishing liquid according to claim 9, characterized in that The ultra-small cerium oxide polishing abrasive has a mass concentration of 0.15% to 0.5% in the polishing liquid, and a pH value of 4 to 5.

Citation Information

Patent Citations

  • Metal doped cerium oxide compositions

    CN106458627A

  • Preparation method and application of lanthanide series metal-doping cerium dioxide nanometer abrasive particles

    CN108410424A

  • Application of cerium oxide nano-particles in preparation of medicine for enhancing cytotoxic CD8 + T cell activity

    CN113116924A

  • Preparation method of spherical cerium-based abrasive material with high hardness and high Ce &lt; 3 + &gt; content

    CN119081650A

  • Methods of polishing an object using slurry compositions

    US20100003897A1